BRANCH RETINAL VEIN OCCLUSION AND ITS AYURVEDIC MANAGEMENT- A CASE STUDY - Bhagwat, Pranav (International Journal of Ayurveda and Pharma Research, 2020)
Branch retinal venous occlusion is second most common vascular disorder found in retina. It usually forms due to venous obstruction at arteriovenous crossing. The arteriolar thickening plays a major role in obstructing the venous return from retina. This can lead to retinal non perfusion area and even macular edema or vitreous haemorrhage, seriously hampering vision. In this paper, I have presented a case of a young man suffering from BRVO and was treated with the help of Ayurvedic medicines. The man presented with field defects and blurred vision. After proper evaluation of Hetus (etiological factors in patient) and Laxanas (clinical features), Samprapti (disease process) was plotted and the diagnosis of Netragata Kafajavatarakta was made. The treatment prescribed was Kafaghna and Vatarktaghna medicines such as Kaishorguggulu, Vasaguluchyadi Kashaya, Punarnava Kashaya, Bidalaka and lifestyle changes. The fundus photographs were taken before and after treatment. Though the patient was irregular in taking medicines, he was completely recovered.